On the significance of different facial parts for automatic age estimation - Lanitis, Andreas (My University, 2002)
In this paper we describe an experimental investigation into the significance of different facial parts in the task of age estimation. For this purpose we use an automatic age estimation algorithm capable of producing an estimate of the age of a subject based on his/her face image. We perform automatic age estimation experiments using different facial parts of varying resolution so that the significance of facial parts in this application can be assessed. According to the results obtained, the internal part of the face and in particular the area around the eyes proved to be the most significant for the task of automatic age estimation.
Keywords: Computing and Processing; Signal Processing and Analysis; Components, Circuits, Devices and Systems; Shape; Aging; Magnetic heads; Face recognition; Human computer interaction; Biological system modeling; Biological systems; Computer science; Educational institutions; Eyes